The Porphyromonas gingivalis inhibitory effects, antioxidant effects and the safety of a Sri Lankan traditional betel quid - an in vitro study - Madhavi Priyanka Paranagama; Nadisha Sewwandi Piyarathne; Tharanga Lakmali Nandasena; Sumedha Jayatilake; Ayanthi Navaratne; Bandula Prasanna Galhena; Senani Williams; Jayantha Rajapakse; Kiyoshi Kita (BMC, 2020)
Abstract Background The Sri Lankan traditional betel quid (TBQ) which had been extensively used in the country before its colonization is claimed to have antiperiodontopathic effects in the Sri Lankan folklore. However, there is no reported scientific evidence to support the claimed antiperiodontopathic effects mediated by this TBQ. The present study was carried out to investigate the protective effect of the Sri Lankan TBQ in the pathogenesis of periodontitis. Methods We investigate the ethyl acetate extract of the Sri Lankan TBQ for its antibacterial effects against the keystone periodontopathic bacterium, P. gingivalis and also its antioxidant potential, which is important to protect the periodontium from oxidative stress. Further, its safety was analyzed using the cytokinesis block micronucleus assay on human peripheral blood lymphocytes (PBLs). Results Ethyl acetate extract of this TBQ inhibited the growth of P. gingivalis with a minimum bactericidal concentration (MBC) of 125 μg/ml. It was found to be a rich source of polyphenols and displayed considerable DPPH and ABTS radical scavenging activities and a strong ferric reducing antioxidant power. This extract could protect the cultured human gingival fibroblasts from H2O2 induced oxidative stress. In addition, this TBQ extract was not genotoxic to human PBLs even at a concentration of 2.5 mg/ml. Moreover, it exhibited protective effects against bleomycin induced genotoxicity in PBLs. Conclusion Ethyl acetate extract of the Sri Lankan TBQ is a source of natural antibacterial compounds against P. gingivalis. It is also a source of natural antioxidants which can protect human gingival fibroblasts from H2O2 induced oxidative stress. These properties of the TBQ may have contributed to its claimed antiperiodontopathic effects. Besides, it was found to be relatively non-toxic to human cells. Thus this TBQ extract has a huge potential to be developed as a novel adjunctive therapeutic lead against periodontitis.